Comparison of an Avian Osteopetrosis Virus with an Avian Lymphomatosis Virus by RNA-DNA Hybridization - Smith, Ralph E. (1976)
Myeloblastosis-associated virus (MAV)-2(0), a virus which was derived from avian myeloblastosis virus and induced a high incidence of osteopetrosis, was compared with avian lymphomatosis virus 5938, a recent field isolate which induced a high incidence of lymphomatosis. The following information was obtained. (i) MAV-2(0) induced osteopetrosis, nephroblastoma, and a very low incidence of hepatocellular carcinoma. No difference was seen in the oncogenic spectrum of end point and plaque-purified MAV-2(0). (ii) (125)I-labeled RNA sequences from MAV-2(0) formed hybrids with DNA extracted from osteopetrotic bone at a rate suggesting five proviral copies per haploid cell genome. The extent of hybridization of MAV-2(0) RNA with DNA from osteopetrotic tissue was more extensive (87%) than was observed in reactions with DNA from uninfected chicken embryos (52%). (iii) Competition of unlabeled viral RNA in hybridization reactions between the radioactive RNA from the two viruses and their respective proviral sequences present in tumor tissues showed that 15 to 20% of the viral sequences detected in these reactions were unshared. In contrast, no differences were detected in competition analyses of RNA sequences from the two viruses detected in DNA of normal chicken cells. (iv) MAV-2(0) 35S RNA was indistinguishable in size from avian lymphomatosis virus 5938 35S RNA by polyacrylamide gel electrophoresis.